2020
DOI: 10.1097/sla.0000000000003821
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Prevention of Anastomotic Recurrence by Excluding Mesentery in Crohn's Disease: The SuPREMe-CD Study - A Randomized Clinical Trial

Abstract: Objective: This trial aimed to provide randomized controlled data comparing Kono-S anastomosis and stapled ileocolic side-to-side anastomosis. Background: Recently, a new antimesenteric, functional, end-to-end, hand-sewn ileocolic anastomosis (Kono-S) has shown a significant reduction in endoscopic recurrence score and surgical recurrence rate in Crohn disease (CD). Methods: Randomized controlled trial (RCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 26 publications
5
129
0
6
Order By: Relevance
“…Participant characteristics are given in Table 2. For the analysis involving the Kono‐S anastomosis, the studies involving a comparator included end‐to‐end [15] or side‐to‐side anastomoses [32] or both [8]. For the analysis involving mesenteric excision, the comparator was preservation of the mesentery (division of the mesentery flush with the intestine).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant characteristics are given in Table 2. For the analysis involving the Kono‐S anastomosis, the studies involving a comparator included end‐to‐end [15] or side‐to‐side anastomoses [32] or both [8]. For the analysis involving mesenteric excision, the comparator was preservation of the mesentery (division of the mesentery flush with the intestine).…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic recurrence was significantly lower in the Kono‐S group compared to the standard anastomosis group. Results from the RCT [32] showed a mean Rutgeerts score of i,1.05 ± 1.06 at 18 months for the Kono‐S group compared with i,2.30 ± 1.32 in the conventional group. A Rutgeerts score of above i,2, indicating a higher risk of symptomatic recurrence, was seen in 9/36 patients (25%) after a Kono‐S anastomosis compared with 29/43 (67.4%) in the conventional anastomosis group.…”
Section: Resultsmentioning
confidence: 99%
“…Shimada N et al reported that the 5-year surgery-free survival rate at the site of anastomosis in patients who underwent Kono-S anastomosis (95%) was signi cantly higher as compared to those who received an end-to-end anastomosis procedure (81.3%; p<0.001) [11]. Furthermore, in the rst randomized clinical trial to compare Kono-S and conventional side-to-side anastomosis procedures in CD patients, Luglio G et al reported results demonstrating a signi cant reduction in postoperative endoscopic and clinical recurrence rates for patients who underwent Kono-S anastomosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…With this technique, the supporting column prevents distortion and keeps the intestinal tract in the anastomosis region straight, which also makes endoscopic examination and balloon dilatation following surgery easier to perform. Shimada N et al reported that the 5-year surgery-free survival rate at the site of anastomosis in patients who underwent Kono-S anastomosis (95%) was signi cantly higher as compared to those who received an end-to-end anastomosis procedure (81.3%; p<0.001) [11]. Furthermore, in the rst randomized clinical trial to compare Kono-S and conventional side-to-side anastomosis procedures in CD patients, Luglio G et al reported results demonstrating a signi cant reduction in postoperative endoscopic and clinical recurrence rates for patients who underwent Kono-S anastomosis [12].…”
Section: Discussionmentioning
confidence: 99%